Red kayaks and hidden gold - Kelly, J (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford, 2009)
This report looks at the growing influence of ‘citizen journalism’, made possible by new technology available to all, and questions the relationship between both the journalist and the public in generating the news today.